1999
DOI: 10.1111/j.1365-2621.1999.tb15055.x
|View full text |Cite
|
Sign up to set email alerts
|

Highly Concentrated Branched Oligosaccharides as Cryoprotectant for Surimi

Abstract: Freeze-thawing studies at different concentrations, using an actomyosin solution (extracted from Alaska pollock), revealed that an 8% (w/v) solution of oligosaccharides mixture (HBOS) was most effective in cryoprotection. During frozen storage (-18°C), HBOS showed cryoprotective effects similar to sucrose and a sucrose+sorbitol mixture (1:1). Surimi gel prepared with HBOS showed higher hardness and more dense microstructure than others, although water holding capacity was slightly lower than the gel with sucro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 23 publications
1
36
0
Order By: Relevance
“…Carvajal et al (1999) revealed the ability of maltodextrins of varying mean molecular weight (versus sucrose or a sucrose-sorbitol mixture) to stabilize Alaska pollock surimi proteins to the denaturing effects of frozen storage. Furthermore, highly concentrated branched oligosaccharides were used as cryoprotectants for surimi by other researchers (Auh et al, 1999).…”
Section: Stabilization Of Protein In Surimimentioning
confidence: 99%
“…Carvajal et al (1999) revealed the ability of maltodextrins of varying mean molecular weight (versus sucrose or a sucrose-sorbitol mixture) to stabilize Alaska pollock surimi proteins to the denaturing effects of frozen storage. Furthermore, highly concentrated branched oligosaccharides were used as cryoprotectants for surimi by other researchers (Auh et al, 1999).…”
Section: Stabilization Of Protein In Surimimentioning
confidence: 99%
“…Myofibrillar protein denaturation during frozen storage expressed by the loss of protein solubility is a result of hydrogen or hydrophobic bonds formation, as well as of that of disulfide bonds, and of ionic interactions (Sych et al 1990(Sych et al , 1991MacDonald & Lanier 1991;Auh et al 1999). SEP of WBM decreased quasi linearly as a function of storage time.…”
Section: Salt Soluble Proteins (Sep)mentioning
confidence: 99%
“…A cryoprotectant is a substance that is used to protect biological tissue from freezing damage, which has been reported to slow down the rate of ice crystal growth and alter crystal shapes (Sych et al 1990 andAlvarez et al 2010). The most commonly used cryoprotectants in the surimi industry have been low molecular weight sugars and polyols, such as sucrose and/or sorbitol, typically added at 8% (w/w) alone or in mixture 1:1 to leached fish muscle (Auh et al 1999). Therefore, the objective of this study was to investigate the effect of cryoprotectants composition on physico-chemical characteristics of spent laying hen breast surimi for improvement of unpopular meat consumption.…”
Section: Introductionmentioning
confidence: 99%